أثر التطورات المصرفية الإلكترونية على إدارة المخاطر الائتمانية باالبنوك التجارية الجزلئرية - عمرون عزيزة (جامعة محمد بوضياف المسيلة, 2015)
Abstract The last quarter of the twentieth century has seen many rapid and profound changes and that because of the technological developments and information that have taken place in the world, affecting the nature of administrative functions and activities of banks, as well increasing the need for policies and new methods for the management of credit risks. The goal of this study is to identify the impact of electronic banking developments on the credit risk management, in the Algerian commercial banks, by using the interview, which was conducted with members of the surveyed banks, the results of the study showed that a lack of private banking risk management organizational department, and the weakness of mechanisms and tools used in credit risk management in banks and non-banking operations based on the various entrances to the modern.
دراسة حالة: عينة من البنوك التجارية بولاية المسيلة
Keywords: globalization of banking, information technology, anking information systems, risk management, electronic development , Electronic banking.